Reward Sensitivity Enhances Ventrolateral Prefrontal Cortex Activation during Free Choice - Cho, Catherine; Smith, David V.; Delgado, Mauricio R. (Frontiers in Neuroscience, 2016)
Expressing one’s preference via choice can be rewarding, particularly when decisions are voluntarily made as opposed to being forced. An open question is whether engaging in choices involving rewards recruits distinct neural systems as a function of sensitivity to reward. Reward sensitivity is a trait partly influenced by the mesolimbic dopamine system, which impacts individuals’ neural and behavioral responses to reward cues. Here, we investigated how reward sensitivity contributes to neural activity associated with free and forced choices. Participants underwent a simple decision-making task, which presented free- or forced-choice trials in the scanner. Each trial presented two cues that were predictive of rewards with different attributes (points or information). Participants could earn points or information by making a choice in each trial to obtain a monetary reward at the end of the experiment. In free-choice trials, participants were offered the opportunity to choose between different reward cues (i.e., points or information), whereas forced-choice trials forced individuals to choose within a given reward cue (i.e., information or information). We found enhanced VLPFC activation during free choice compared to forced choice in individuals with high reward sensitivity scores. Next, using the VLPFC as a seed, we conducted a PPI analysis to identify brain regions that enhance connectivity with the VLPFC during free choice. Our PPI analyses on free vs. forced choice revealed increased VLPFC connectivity with the posterior cingulate and precentral gyrus in reward sensitive individuals. These findings suggest reward sensitivity may recruit attentional control processes during free choice potentially supporting goal-directed behavior and action selection.